Enhanced electronic and nonlinear optical responses of C24N24 cavernous nitride fullerene by decoration with first row transition metals; A computational investigation. (16th May 2020) - Shakerzadeh, Ehsan; Mashak Shabavi, Zahra; Anota, Erneto Chigo
Abstract : The electronic (energy gap and work function) as well as electrical properties (dipole moment, polarizability, and first hyperpolarizabilities) of the first‐row transition metals decorated C24 N24 cavernous nitride fullerene were explored using DFT calculations. The transition metals are decorated at N4 cavity of C24 N24 fullerene. According to our spin polarized computations, the most stable spin state monotonically increases to sextet for Mn@C24 N24 and thereafter dropped off gradually to singlet state for Zn@C24 N24 system. The findings demonstrate that transition metals can remarkably decrease the HOMO‐LUMO energy gap and work function values up to 63% and 21% of bare C24 N24, respectively. As can be seen, when the Sc and Ti metals are located above the N4 cavity of fullerene, systems of enhanced static hyperpolarizabilities ( β 0 ) are delivered. These findings might provide an effective strategy to design high performance eletcro‐optical materials based on carbon‐ nitride fullerene. Abstract : TM@C24 N24 fullerenes are investigated for electronic and NLO properties through DFT and TD‐DFT calculations. The electro‐optical properties of C24 N24 fullerenes are very sensitive to transition metals decoration.